Blind Special Education Students Learning: Preparing Future Teachers Psychology - Mohd Norazmi, Nordin; Madzlan, Abet; Doris, Maying; Tang, Hung Moi; Mohd Saleh, Abas (2023)
This study investigates how 41 pre-service language instructors from the US, Poland, and China (CN) worked together for seven weeks to teach English grammar using computer-aided language learning (CALL). Students from the United States and other countries took part in a tele-collaboration effort to teach grammar to their worldwide peers. Pre-service teachers were surveyed about their grammar teaching methods and how they responded to them, along with their views on the value of tele-collaboration for teaching and learning grammar. Researchers found that (1) implicit teaching techniques were used the most frequently; (2) grammatical forms employed by both implicit and explicit teachers were reflective of the communicative orientation of their exchanges; and (3)learners' uptake (attempts to follow grammatical models provided in input) and the forms they paid attention to reflected their proficiency levels. According to the data, online interactions may assist prospective teachers get hands-on experience teaching communicative grammar.